Resilient control design for networked DC microgrids under time-constrained DoS attacks. (August 2022) - Hu, Songlin; Yang, Fuyi; Gorbachev, Sergey; Yue, Dong; Kuzin, Victor; Deng, Chao
Abstract: This paper studies the resilient current controller design for the networked DC microgrid system with multiple constant power loads (CPLs) under a new type of time-constrained denial-of-service (DoS) attack. Different from the existing DoS attack models, which are often characterized by DoS frequency and DoS duration, this paper only considers the duration characteristics of the sporadic/aperiodic DoS attacks, and proposes a new type of time-constrained DoS attack model. Under the effects of such DoS attacks, a switching state feedback control law is constructed and a switching-like DC microgrid system model is then established. Furthermore, based on an attack-parameter-dependent time-varying Lyapunov function (TVLF) method, the exponential stability criterion of the resulting DC microgrid system under aperiodic DoS attacks is derived, and a new resilient controller design method is proposed. Finally, simulation studies are given to verify the effectiveness and merits of the proposed resilient control design scheme on achieving the desired control performance and attack resilience. Highlights: In contrast to [19], the proposed DoS attack model does only require to know the uniform lower and upper bounds on the sleeping and active periods of the attacks, respectively. Different from [19-21], in this paper, an attack-parameter-dependent TVLF method is used to obtain the exponential stabilization conditions of the considered DC microgrid. The proposed resilient controller design procedure is non-conservative, implying that we obtain the optimal controller without any estimation like [20] or approximation [21].